Bufalin inhibits gefitinib resistant NCI-H460 human lung cancer cell migration and invasion in vitro. (24th December 2016) - Huang, An-Cheng; Yang, Mei-Due; Hsiao, Yung-Ting; Lin, Tzu-Shun; Ma, Yi-Shih; Peng, Shu-Fen; Hsia, Te-Chun; Cheng, Yih-Dih; Kuo, Chao-Lin; Chung, Jing-Gung
Abstract: Ethnopharmacological relevance: Bufalin, a component of Chan Su (frog), has been shown to have biological activities including anti-tumor effects. Gefitinib has been used as an anti-cancer drug in lung cancer patients; however, some patients eventually become gefitinib resistant. Aim of the study: In this study, we investigated anti-metastasis effects of bufalin in gefitinib resistant NCI-H460 lung cancer cells. Materials and methods: The effects of the bufalin in gefitinib resistant NCI-H460 lung cancer cells were investigated on cell viability using flow cytometry. The adhesion capacity, wound healing assay, invasion and migration assay, and Western blot analysis were used to understand the molecular mechanisms in this study Results: Under sub-lethal concentrations (from 2.5 up to 10 nM), bufalin significantly inhibits cell adhension, migration and invasion nature of gefitinib resistant H460 cells. Western blotting assay revealed that bufalin depressed some of the key metastasis-related proteins, such as SOS-1, MMP-2 and Rho A underwent significant reduction. Phosphorylated Focal adhesion kinase (p-FAK), phosphorylated extracellular signal-regulated kinase (p-ERK1/2), Ras and E-cadherin were significantly reduced at 48 h treatment. However, phosphorylated p38 (p-p38), phosphorylated c-Jun NH2-terminal kinase (p-JNK1/2) and NF-κBp65 were increased. Conclusions: Based on these observations, we suggest that bufalin can be used in anti-metastasis of gefitinib resistant NCI-H460 lung cancer cells in the future. Graphical abstract: